Screening for the bioactive constituents of traditional Chinese medicines—progress and challenges. Issue 6 (13th January 2017) - Yang, Xing-Xin; Gu, Wen; Liang, Li; Yan, Hong-Li; Wang, Yan-Fang; Bi, Qian; Zhang, Ting; Yu, Jie; Rao, Gao-Xiong
Abstract : The search for lead compounds from traditional Chinese medicines (TCMs) may be promising for new drug development. Abstract : The search for lead compounds from traditional Chinese medicines (TCMs) may be promising for new drug development. Screening efficiency and efficacy is chiefly determined by the validity of the selected screening tools. Recently, many experimental screening tools have been developed to identify lead compounds. This review provides a toolbox of the experimental screening methods and models that have been applied to discover new lead compounds and drugs from TCMs. The merits and limitations of these tools are summarized, assisting readers in the rapid retrieval of useful information and providing reference values for selecting appropriate screening tools for different research.